STRATEGI NATION BRANDING THAILAND MELALUI AMAZING THAILAND DALAM MEMPROMOSIKAN PARIWISATA NASIONAL DI SINGAPURA (2019-2023) - Febryani, Felly; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research will analyse and describe the nation branding strategy through initiatives undertaken by the Thai government in branding the country through Amazing Thailand as a tourism campaign, especially in promoting the national tourism industry in Singapore. Seeing that in a certain period of time there was a decline in Singaporean tourist visits to Thailand. The Amazing Thailand campaign is an effort to re-enhance Thailand's image to Singaporeans who want to visit Thailand. This research uses a pluralism perspective and is analysed based on the theory and concept of nation branding by Keith Dinnie through his book entitled